Perioperative management of severe factor VII deficiency: a single-center experience in China - Zhu, Chao; Zhao, Jinxia; Xu, Longqiang; Lu, Wenfei; Liu, Shiguo; Guan, Jialiang (Frontiers in Medicine, 2025)
IntroductionInherited factor VII (FVII) deficiency is a rare autosomal recessive disorder whose clinical phenotypes are highly variable. Many studies have observed the absence of a clear-cut and consistent correlation between bleeding symptoms and FVII levels. Perioperative bleeding is a major concern in patients with FVII deficiency, but validated recommendations about the perioperative management of replacement therapy (RT) with FVII are lacking.MethodsOur study retrospectively summarized and analyzed the perioperative hemostasis management of severe FVII deficiency in 20 patients.ResultsWe found that replacement therapy is generally effective and that there is no significant correlation between the perioperative hemorrhagic complications after RT and the severity of FVII level before RT. Through multivariate statistical analysis and a retrospective analysis of other coagulation factor deficiencies at our center, we found that postoperative secondary hyperfibrinolysis in patients with FVII deficiency may not be universal.DiscussionAntifibrinolytic treatment may be necessary for patients undergoing surgery at sites with high fibrinolytic activity during the perioperative period. In addition, clinical data such as bleeding phenotype, bleeding history, and surgical sites should be given appropriate attention in perioperative treatment and monitoring.